Public Infrastructure as a Determinant of Intertemporal and Interregional Productive Performance in China - Feng-Cheng Fu; Chu-Ping C. Vijverberg; Wim P. M. Vijverberg (Institute for the Study of Labor (IZA), 2004)
This paper focuses on the question whether public infrastructure capital matters for labor productivity in China, both over time and across regions. It finds that public infrastructure is a significant determinant of variations in labor productivity across provinces, but the contribution of public capital to labor productivity growth over time is likely non-existing or even negative. These seemingly contradictory results are reconciled once we view the measured intertemporal effect as a short-run impact and the interregional effect as a longterm consequence of public infrastructure investment.
Keywords: O47; H54; R11; 330; public infrastructure; labor productivity; China; Infrastruktur; Arbeitsproduktivität; Region; China